(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction:Drowning is the 3rd leading cause of unintentional injury deaths.As drowning is a preventable cause of mortality, our aims for the benefit of society at large is to minimize the events as far as possible. Objective:A clear knowledge about factors which play a major role behind such incidences is important.It has equal forensic importance as determination of cause and manner of death require thorough investigation. Methodology: We conducted one-year study of demographic variables and the histopathological changes in relation to lung and splenic tissues in cases of drowning deaths, in the hot and humid climatic region of Eastern India.Results: The demographic findings were presented in graphs and charts. However, none of the commonly known autopsy findings (histopathological) are found to be individually confirmatory of drowning. Conclusion:Several factors inclusive of autopsy findings, biochemical examination, radiological and molecular technique,are needed to be taken together as complementary methods to conclude drowning as the cause of death when bodies are recovered from water.